PENDEKATAN KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN APRESIASI SENI MAHASISWA PGSD FKIP UNIVERSITAS RIAU - antosa, zariul (LPPM Undiksha, 2017)
The problem inthis studyis the lack ofability to appreciate the art work on PGSD FKIP-UR students who can be seen insymptoms symptoms of inability to distinguish works of craft and art works, the low ability students explain the function and meaning of craft objects in public life in accordance with the local culture local. Lack of student awards both morally and materially to the creation of creative crafts. lack of abilityin the understanding of concepts, reasoning, and problem solving, artcrafts. Based on the problems it is necessary to find away to solve the problem. Among themis to change the methods of teaching. For that in this study the researcher will apply local knowledge in the learning approach. This research was conductedasa classaction two cycles each cycleconsisted of two meetings. The application of local wisdom approach in volvesa conscious effort to engage students actively and creatively. Subjects in this study were students PGSD FKIP-UR fourth semester. Research data collection instruments consisted of observation activity sheets and sheets of faculty and students to replay the end of thetest cycle. The study was a classroom action research (CAR), this study aims to increase art appreciation fourth semester students PGSDFKIP-UR. The results of this study indicate that the application of local wisdom approach can improve student art appreciation PGSD FKIP-UR, with the average value of the initial value of 58.41 into a 84.75 in the second cycle. The average value of faculty activity also increased from an average of68.15 into 94.75. Student Activities also increased from an average of 63.24% in the first cycle to 89.80%. Thus,the research hypothesis when applied local wisdom, the ability to approa chart appreciation PGSD FKIP-UR students increased, proven